Crop insurance and crop productivity: Evidence from rice farmers in eastern India - Kumar, Anjani; Saroj, Sunil; Mishra, Ashok K. (International Food Policy Research Institute, 2021)
The paper explores the spread of crop insurance in India and analyzes the factors affecting the demand for crop insurance. The study also assesses the impact of crop insurance on the rice yields of smallholder rice producers. Using data from a large farm-level survey from eastern India, the study tests for robustness of the findings after controlling for other covariates and endogeneity, using propensity score matching, coarsened exact matching, and endogenous switching regression models. Results indicate a positive and significant impact of crop insurance on rice yields.